A Time to Print, a Time to Reform - Lars Boerner; Jared Rubin; Battista Severgnini (Copenhagen Business School (CBS), Department of Economics, 2019)
The public mechanical clock and the movable type printing press were two of the most important and complex general purpose technologies of the late medieval period. We document two of their most important, yet unforeseeable, consequences. First, an instrumental variables analysis indicates that towns that were early adopters of clocks were more likely to also be early adopters of presses. We posit that towns with clocks became upper-tail human capital hubs - both technologies required extensive technical know-how that had many points of overlap. Second, a three-stage instrumental variables analysis indicates that the press influenced the adoption of Lutheranism and Calvinism, while the clock's effect on the Reformation was indirect (via the press).
hdl:10398/9731
Keywords: N33; N73; O33; O34; P48; Z12; 330; mechanical clock; printing press; technology; Reformation; human capital; Calvinism; Lutheranism; instrumental variables